Isolation and Identification of Aroma-producing Yeast from Mackerel Fermentation Broth and Its Fermentation Characteristics - Wu, Yu; Chen, Xiao'e; Fang, Xubo; Ji, Lili; Tian, Fang; Yu, Hui; Chen, Yan (Journal of aquatic food product technology, 2021)
In order to obtain microbial starter cultures for aroma enhancement of fish sauce, aroma-producing yeasts from mackerel fermentation broth were isolated, screened and identified by morphological characterization and ITS rDNA sequence analysis. The results showed that seven yeast strains were isolated, of which six strains were Lodderomyces elongisporus and one was Wickerhamomyces anomalus. The volatile compounds of mackerel enzymatic hydrolysate fermented by the yeasts were analyzed by headspace solid phase micro extraction and gas chromatography coupled with mass spectrometry (HS-SPME/GC-MS). The results indicated that the main volatile compounds were aldehydes, ketones, alcohols, esters, hydrocarbons, acids and heterocycles in the fermentation broths, rendering the special aroma and flavor of fish sauce. In addition, the growth assay, salt tolerance and temperature resistance of the two yeast strains were determined, which was found that the strains exhibited excellent salt tolerance and temperature resistance. For the first time, Wickerhamomyces anomalus and Lodderomyces elongisporus were separated from the aquatic products, exhibiting enormous potential in the application of the aroma-enhancing for fish sauce.